Community-based family and carer-support programmes for children with disabilities. Issue 5 (May 2020) - Heys, Michelle; Lakhanpaul, Monica; Allaham, Shereen; Manikam, Logan; Owugha, Jessica; Oulton, Kate; Morris, Christopher; Martin, Karen R.; Tann, Cally; Martin, Jennifer; Kuper, Hannah
Abstract: Children and young people (CYP) with disabilities face multiple challenges and unmet health needs. There is considerable variability in quality of health services across the UK for these children. Families report that they experience lack of information or misinformation about health, social care and education of their child. They also highlight a desire to engage with other families of CYP with disabilities. There is growing evidence that community-based group interventions in under-resourced settings are effective at improving quality of life for both CYP with disabilities and caregivers. Few similar interventions or evidence exists in the UK. This article provides an overview of relevant evidence and, using cerebral palsy as an exemplar, discusses the potential for group-based programmes for parent carers in the UK. Groups would aim to address information needs, support providers to deliver evidence-based care, and thereby improve the health and wellbeing of CYP with disabilities.